ACT-1 A PROSPECTIVE MULTICENTER PHASE I/IIA STUDY OF PREOPERATIVE NEOADJUVANT BEVACIZUMAB FOR NEWLY DIAGNOSED GLIOBLASTOMA. (3rd December 2022) - Tanaka, Toshihide; Tamura, Ryota; Takei, Jun; Morimoto, Yukina; Teshigawara, Akihiko; Tohmoto, Kyoichi; Kuranari, Yuki; Imai, Ryotarou; Yamamoto, Yohei; Hasegawa, Yuzuru; Akasaki, Yasuharu; Murayama, Yuichi; et al.
Abstract: Background: Preoperative neoadjuvant bevacizumab (neoBev) reduces enhancement and perifocal edema by inhibition of angiogenesis and vascular permeability for glioblastoma (GBM). The aim of this study was to investigate safety and efficacy of neoBev for newly diagnosed GBM through an exploratory prospective multi-center study. METHODS & PATIENTS: 15 patients with newly diagnosed GBM were enrolled in the present study. Eligibility was a patient with a brain tumor representing with ring-shaped enhancement and perifocal edema on magnetic resonance imaging (MRI). Based on neuroimage of typical GBM, neoBev and temozolomide (TMZ) were administered prior to craniotomy. Two weeks after neoBev, the tumor volume on T1-weighted gadolinium enhancement (T1Gd) and fluid attenuated inversion recovery (FLAIR) were assessed. Three to four weeks after neoBev and TMZ administration, patients underwent surgical resection. The primary endpoint was feasibility and safety, and the secondary endpoint was efficacy. Adverse events including systemic toxicity and wound healing delay during radiation (RT), TMZ, and Bev combined therapy were carefully monitored throughout clinical course including extent of resection. RESULTS: Average of tumor regression rate two weeks after neoBev on T1Gd and FLAIR were 37.0% and 54.0%, respectively. Cerebral blood flow and cerebral blood volume were reduced after neoBev. Patients underwent surgical resection safely without excess blood loss due to less vascular and less degree of brain swelling. Two patients underwent awake surgery without any complications. Postoperative MRI showed that the all tumors were totally removed except one with multiple invasive tumors. Histological diagnosis of all patients was GBM, IDH-1 wild-type. Postoperative course was uneventful without neurological deficit and adverse effects except one postoperative hematoma in the resection cavity and one wound infection due to wound dehiscence. CONCLUSION: Preoperative neoBev for newly diagnosed GBM might contribute to safe surgery. Clinical outcome of this therapeutics is now currently under investigation.